Processing map and hot working mechanisms of Cu-Ag alloy in hot compression process - Wang, Meng-han; Huang, Long; Chen, Ming-liang; Wang, Yan-li (Journal of Central South University, 2015)
For Gu-Ag alloy, an important parameter called workability in the forming process of materials can be evaluated by processing maps yielded from the stress-strain data generated by hot compression tests at temperatures of 700–850 °C and strain rates of 0.01–10 s −1 . And at the true strain of 0.15, 0.35 and 0.55, respectively, the responses of strain-rate sensitivity, power dissipation efficiency and instability parameter to temperature and strain rate were studied. Instability maps and power dissipation maps were superimposed to form processing maps, which reveal the determinate regions where individual metallurgical processes occur and the limiting conditions of flow instability regions. Furthermore, the optimal processing parameters for bulk metal working are identified clearly by the processing maps.